The Effect Of Learning Approaches And Learning Creativity On The Ability To Solve Physic Problems - Popi Purwanti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The purpose of this study is to determine the differences in the effect of students' ability to solve physics problems between those taught with the Scientific learning approach and the conventional learning approach. Knowing the difference in the ability to solve physics problems between students who have high creativity and students who have low creativity. Then find out the effect of the interaction between the learning approach and learning creativity on the ability to solve physics problems.The research method used is experiment. The sample size was 80 students consisting of 40 students in the experimental group and 40 students in the control group selected by cluster sampling. Data collection was carried out with the technique of giving 10 items of test description and 30 items of learning creativity questionnaire. Data analysis using descriptive statistical methods and data requirements analysis. Test the hypothesis of this study using two-way ANAVA. The results showed that: (1) There is a difference in the ability to solve the physics problems of students who are taught with a scientific learning approach and those taught with a conventional learning approach.(2) There is a difference in the ability to solve physics problems of students who have high creativity and students who have low creativity.(3) There is no influence of the interaction of learning approaches with learning creativity.In this study shows that the approach to scientific learning is better than conventional learning approaches. This means that by applying a scientific learning approach and paying attention to student learning creativity well, it will produce the ability to solve good physics problems